Comparison of Shear Bond Strength of Self-Adhesive Resin Cement and Conventional Resin Cement Bonded to Lithium Disilicate Glass Ceramic with Different Surface Treatments: In Vitro Study - Mumtaz A. Sadeeq; Abdulkareem R. Ibrahim (University of Mosul, College of Dentistry, 2024)
Aims: to measure the shear bonding strength of self-adhesive resin-cement bonded to lithium disilicate glass-ceramic with different surface treatments and compare it with that of conventional resin-cement. Materials and Methods: eighty circular blocks (10mm-diameter x 3.0mm-thickness) of IPS e-max Press ceramic, were fabricated in accordance with the manufacturer's instructions. The samples were divided into four main groups (n=20) according to surface treatments: group A no surface treatment, group B sandblasting with 50-μm alumina particles for five seconds under two-bars of pressure using a sandblasting device, group C acid-etching with 9% hydrofluoric acid for 20-seconds, followed by rinsing with distilled water, group D combination by sandblasting with 50-μm alumina particles as in group B and then were etched with 9% hydrofluoric acid as in group C. For the bonding procedure, each main group was divided into two subgroups (n=10) according to the types of resin cement that were used: sub-group1: specimens were prepared by applying one layer of silane on the ceramic surface. Then single bond universal was applied by micro-brush. Then specimens were light cured, next, 2-mm-long transparent plastic tubes with 4-mm diameter were placed on the ceramic surface, and filled with conventional resin-cement, it was light-cured, sub-group2: 2-mm-long transparent plastic tubes with 4-mm diameter were placed on the ceramic surface and filled with self-adhesive resin-cement, then were light-cured, and the shear bond strength was tested using the universal testing machine. The results were analyzed statistically. Results: Comparisons of shear bonding strength between total conventional and self-adhesive groups show that the highest mean was in the conventional adhesive group (49.13 ±3.05), while the lowest mean was in the self-adhesive group (26.51 ±2.16). Conclusions: With all surface treatments, self-adhesive resin-cement had a lower mean shear bond strength than conventional resin-cement.